Transmissão intersetorial dos ganhos de produtividade: evidências para o Brasil no período 2000-2009 - Gazonato, Mariana Camarin (2016)
The main purpose of this dissertation is to analyze the capacity of sectors of the Brazilian economy to tranfer their productivity gains over the production chain, in the period 2000-2009. In this way, an adjustment is performed, through the structural decomposition technique of the input-output analysis of Dietzenbacher and Los (1998), of the method proposed by Greenhalgh e Gregory (2000). The fundamental assumptions, based on the structuralist current, are that the Industry tends to have larger increases in productivity and linkages with other segments of the economy, especially when compared to the Services. Together, these attributes would make that the productivity gains of the industrial sector propagate more intensely by the productive chain. The results show that in the period analyzed, the Agricultural and Services were the primarily responsible for transmiting these increments for the rest of the economy, instead of Industry, which moved forward losses of productivity. However, despite the Services have become more productive and transferred these gains over the production chain, the average transmission power of its segments was relatively low compared to the Industry's ability to transmit forward its productivity losses. This is because a considerable portion of the increments of the tertiary sector occurred in Personal Services, segment with reduced links in the production chain and whose goods meet, mainly, the individual consumer. The fact that the Industry ´s power transmission is, on average, higher than that of Services implies that if the industrial sector had increase its productivity, rather than decrease it, greater productivity gains would have been transmitted to the other segments of the economy that have been verified by the productivity gains of Services. However, it is important to stress that certain activities of the tertiary sector showed high potential to transfer these increments. This was the case of the Knowledge-Intensive Business Services.